Changes in synovial fluid and serum concentrations of cartilage oligomeric matrix protein over 5 years after anterior cruciate ligament rupture: an exploratory analysis in the KANON trial. Issue 10 (October 2018) - Struglics, A.; Larsson, S.; Pramhed, A.; Frobell, R.; Swärd, P.
Summary: Objective: To monitor longitudinal changes of cartilage oligomeric matrix protein (COMP) in synovial fluid (sf) and serum (s) over 5 years after acute anterior cruciate ligament (ACL) rupture, and to compare results from two commercial COMP immunoassays. Design: Bio-fluids were collected from 121 patients on six occasions over 5 years after acute ACL injury, and from 25 knee healthy reference subjects. Concentrations of sf- and sCOMP were measured by AnaMar (sCOMP-Ana) and by BioVendor (sf- and sCOMP-Bio) immunoassays; other biomarkers were previously assessed. We used ANCOVA for group comparisons and linear mixed models for associations between biomarkers over 5-years with P  < 0.05 considered a statistically significant difference or association. Results: Compared to the reference group, sfCOMP-Bio concentrations were 2-fold elevated within 6 weeks after ACL injury and remained elevated 5 years thereafter, whereas sCOMP-Bio and sCOMP-Ana concentrations were no different from reference levels at any time point. Over the 5-year period, there was an association between sCOMP-Bio and sCOMP-Ana concentrations, although neither sCOMP-Bio nor sCOMP-Ana associated with sfCOMP-Bio. sfCOMP-Bio associated with SF ARGS-aggrecan, urine type I and II collagens (uNTX-I and uCTX-II) and SF cytokines, while sCOMP-Bio associated inversely with uCTX-II, uNTX-I and SF cytokines. Conclusion: The local process after an acute ACL injury generates increased SF COMP concentrations in the injured knee up to 5 years after injury. This response is not detected in serum. Discrepancies in associations between sCOMP measured by BioVendor and AnaMar immunoassays with other biomarkers indicate differences in detected COMP fragments.